MAKNA TOLERANSI DAN MODERASI BERAGAMA DALAM FILM DOKUMENTER - Ihsannulhaq, Pangeran Arsyad; Marini (Komsospol, 2023)
In religious life, everyone is free to choose and carry out worship based on their own beliefs and true beliefs without any intimidation from certain groups. This is also what is reflected in the people of Pekon Ambarawa Pringsewu Lampung who apply various concepts of moderation in their daily lives. There are many religions that live in harmony there, such as Islam, Christianity, Catholicism, Hinduism and Buddhism. Film is one of the propaganda media to convey messages in a contemporary way in society. Apart from being informative and entertaining, packaging da'wah messages through films is also an effective communication medium for the public. Likewise with the documentary film "Selaras" produced by the Nurul Huda Pringsewu Islamic Boarding School which raises the theme of religious moderation in society. The research method uses a qualitative approach with a descriptive method with a constructivism paradigm which aims to find out how the implementation of effective communication is built in the documentary film "Selaras". Based on the research results above, the author concludes that the implementation of effective communication in religious moderation through the documentary film "Selaras" consists of various indicators of religious moderation, such as; National Commitment, Tolerance, Non-Violence, and Acceptance of Tradition. This indicator was conveyed because of effective communication conveyed through film media as a means of disseminating information.